Factors Influencing Laboratory Information System Effectiveness Through Strategic Planning in Shiraz Teaching Hospitals. Issue 1 (January 2018) - Bahador, Fateme; Sharifian, Roxana; Farhadi, Payam; Jafari, Abdosaleh; Nematolahi, Mohtram; Shokrpour, Nasrin
Abstract : This study aimed to develop and test a research model that examined 7effective factors on the effectiveness of laboratory information system (LIS) through strategic planning. This research was carried out on total laboratory staff, information technology staff, and laboratory managers in Shiraz (a city in the south of Iran) teaching hospitals by structural equation modeling approach in 2015. The results revealed that there was no significant positive relationship between decisions based on cost-benefit analysis and LIS functionality with LIS effectiveness, but there was a significant positive relationship between other factors and LIS effectiveness. As expected, high levels of strategic information system planning result in increasing LIS effectiveness. The results also showed that the relationship between cost-benefit analysis, LIS functionality, end-user involvement, and information technology–business alignment with strategic information system planning was significant and positive.